2022
DOI: 10.21103/article12(1)_oa13
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Experimental Colitis Therapy with Original Vitamin D3 Rectal Suppositories

Abstract: Background: Pathogenesis of inflammatory bowel disease (IBD) is insufficiently explored, while most of the therapeutic agents used for IBD cases have undesirable side effects, which restrict their administration.The aim of this research was to study the influence of vitamin D3 formulated into original rectal suppositories on the parameters of clinical score, morphology, and oxidative lipid and protein destruction in the colonic lesion in the cases of experimental colitis (EC). Methods and Results: The experim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0
3

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 0 publications
0
2
0
3
Order By: Relevance
“…EC was modeled by two-stage application of a 3% alcohol solution of oxazolone (4-ethoxymethylene-2-phenyl-2-oxazoline-5-oh). At the first stage, cuta neous sensitization was carried out by applying 675 µl/kg to the interscapular area, at the secondrectal injection of 675 µl/kg into the colon to a depth of 8 cm [8].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…EC was modeled by two-stage application of a 3% alcohol solution of oxazolone (4-ethoxymethylene-2-phenyl-2-oxazoline-5-oh). At the first stage, cuta neous sensitization was carried out by applying 675 µl/kg to the interscapular area, at the secondrectal injection of 675 µl/kg into the colon to a depth of 8 cm [8].…”
Section: Methodsmentioning
confidence: 99%
“…We have developed original rectal suppositories with vitamin D 3 based on a 10% aqueous solution of vitamin D 3 (Patent 20.05.2019). We have previously demonstrated that vitamin D 3 in the original rectal suppositories in experimental colitis (EC) has a local antioxidant effect by limiting the formation of POL and OMB products; a systemic immunotropic effect by reducing the number of neutrophils, restoring the absorption and HCTreducing activity of neutrophils, reducing the number of lymphocytes, including CD3 + and CD45RA + , reducing the concentration of IgM, IgG, IL-6 and IL-8 [8]. We believe that the systemic immunotropic effects of vitamin D 3 in the composition of the original rectal suppositories in EC are due to its local protective effect in the focus of damage to the colon.…”
Section: Introductionmentioning
confidence: 99%
“…Клинико-морфологическая картина поражения толстой кишки при ОИК соответствует изменениям при ВЗК у человека и позволяет применять оксазолоновую модель колита для изучения патогенеза и апробации эффективности применения новых терапевтических подходов при ВЗК [16,17].…”
Section: обсуждение интерпретация / научная значимостьunclassified
“…Нами разработаны оригиналь- ные ректальные суппозитории с витамином D3 на основе 10%-го водного раствора витамина D3 [13]. Ранее нами продемонстрировано, что витамин D3 в составе оригинальных ректальных суппозиториев при экспериментальном колите (ЭК) обладает системным иммунотропным действием за счет снижения количества нейтрофилов, восстановления поглотительной и НСТ-редуцирующей активности нейтрофилов, снижения количества лимфоцитов, в том числе CD3+ и CD45RA+, снижения концентрации IgM, IgG, IL-6 и IL-8 и антиоксидантного действия за счет снижения содержания в стенке толстой кишки продуктов перекисного окисления липидов и продуктов окислительной модификации белков [14,15,16,17,18]. Полагаем, что системные иммунотропные эффекты витамина D3 в составе оригинальных ректальных суппозиториев при ЭК обусловлены его локальным протекторным действием в очаге повреждения толстой кишки.…”
Section: For Citationunclassified